Research of factors influence on the choice of a system for application and installation of pvc windows - OSYPOV, Oleksander; FIRSOV, Dmytro (Ways to Improve Construction Efficiency, 2025)
The active development of the construction industry of Ukraine is carried out through the introduction of modern technologies, adapting to the challenges of the time, in particular, to the needs of post-war reconstruction, renovation of industrial and civil buildings and infrastructure facilities. Technologies in the construction industry of Ukraine are developing due to the introduction of innovative approaches. A significant increase in construction volumes and growing demand for residential buildings also affects the volume of installation work of window structures, which accordingly requires scientific substantiation of possible directions for improving the technological process. The choice of a PVC window structure system and their correct installation are critically important for ensuring comfort, energy efficiency and durability of the building. Indicators such as room sound insulation, energy saving, air exchange, and the climate inside the room and, as a result, human health directly depend on the quality of window installation. Failure to take into account important factors can subsequently lead to negative consequences (namely, drafts, the appearance of mold inside the room, increased air humidity). It has been established that the process of installing window structures is currently characterized as labor-intensive (it has many heterogeneous operations) and is mainly performed manually. However, the development of technology, the appearance of new systems on the market, provides an opportunity to make certain changes and reduce the time of work on the construction site. An important issue is the determination of factors that affect the possibility of choosing the optimal solution. The presence of window blocks prepared for installation and additional installation systems, coordinated work of the team and effective coordination of material supplies minimize downtime and reduce the total installation time. The use of BIM technologies (Building Information Modeling) allows you to plan all stages of work in advance, reducing the number of errors. The conditions of work, type of construction, design solutions, restrictions and organization of construction - all these factors significantly affect the choice of window installation technology and, as a result, the time and cost of construction as a whole.